Strategic investment proposals and the balanced scorecard: how to ensure consistency between investments and long term strategy / Ralph W. Adler, Paul Theivananthampillai - Adler, Ralph W. (Accounting Research Institute, Faculty of Accountancy & UiTM Press, 2006)
This paper examines how a balanced scorecard can be used to guide strategic investment decisions. As noted in then literature, an advantage of the balanced scorecard over the common financial metrics that are often used (e.g., net present value) is that a broader set of benefits and limitations can be recognized. Furthermore, unlike other non-financial and hybrid financial and non-financial approaches, the balanced scorecard provides relatively clear guidance.